Penser la mobilité durable au-delà de la planification traditionnelle du transport - Jade Bourdages; Eric Champagne (VertigO, 2012)
In Quebec, as elsewhere, the integration of the “sustainable mobility” concept in the scientific, political, technical, and citizen vocabulary within the past decade is a turning point. The concept has theoretical implications but it also influences policy making and management practices in the way space and movement in urban environments are managed. If the concept of sustainable mobility is often assimilated to that of sustainable transport in the rhetoric, the scientific literature tells us that such confusion is incorrect. In fact, that conceptual development takes us beyond technological efficiency and the expansion of transportation facilities to ensure acceptable level of social and economic costs associated with the mobility of people and goods. Sustainable mobility is a prelude to new questions that affect the paradigm of "sustainable transport". The concept of sustainable mobility invites us to question the previous technical centered approaches and the conventional approaches that are used to identify, analyze and evaluate transportation planning issues. This article aims to contribute to understanding the different dimensions that covers the concept of sustainable mobility, which requires an effort of clarification. The overall objective of this paper is to highlight the particularities of the “sustainable mobility” concept as opposed to the concept of “sustainable transport”. The relationship and similarities between both concepts will be identified along with the differentiation between them. This analysis will allow us to consider sustainable mobility as a paradigm shift which enjoins us to think of it beyond traditional urban transportation planning approaches.